Oyster Reefs in Northern Gulf of Mexico Estuaries Harbor Diverse Fish and Decapod Crustacean Assemblages: A Meta-Synthesis - La Peyre, Megan K.; Aguilar Marshall, Danielle; Miller, Lindsay S.; Humphries, Austin T. (Frontiers in Marine Science, 2019)
Oyster reefs provide habitat for numerous fish and decapod crustacean species that mediate ecosystem functioning and support vibrant fisheries. Recent focus on the restoration of eastern oyster (Crassostrea virginica) reefs stems from this role as a critical ecosystem engineer. Within the shallow estuaries of the northern Gulf of Mexico (nGoM), the eastern oyster is the dominant reef building organism. This study synthesizes data on fish and decapod crustacean occupancy of oyster reefs across nGoM with the goal of providing management and restoration benchmarks, something that is currently lacking for the region. Relevant data from 23 studies were identified, representing data from all five U.S. nGoM states over the last 28 years. Cumulatively, these studies documented over 120,000 individuals from 115 fish and 41 decapod crustacean species. Densities as high as 2800 ind m-2 were reported, with individual reef assemblages composed of as many as 52 species. Small, cryptic organisms that occupy interstitial spaces within the reefs, and sampled using trays, were found at an average density of 647 and 20 ind m-2 for decapod crustaceans (range: 18 - 2843) and fishes (range: 2 - 56), respectively. Both groups of organisms were comprised, on average, of 8 species (range: 3 - 15). Larger-bodied fishes captured adjacent to the reef using gill nets were found at an average density of 6 ind m-2 (range: 1- 68) which came from 23 species (range: 9 - 46). Decapod crustaceans sampled with gill nets had a much lower average density, < 1 ind m-2, and only contained 2 species. On average, seines captured the greatest number of fish species (n = 33), which were made up of both facultative residents and transients. These data provide general gear-specific benchmarks, based on values currently found in the region, to assist managers in assessing nekton occupancy of oyster reefs, and assessing trends or changes in status of oyster reef associated nekton support. More explicit reef descriptions (e.g., rugosity, height, area, adjacent habitat) would allow for more precise benchmarks as these factors are important in determining nekton assemblages, and sampling efficiency.